2020
DOI: 10.1038/s41467-019-14071-8
|View full text |Cite
|
Sign up to set email alerts
|

Formation of bridgmanite-enriched layer at the top lower-mantle during magma ocean solidification

Abstract: Thermochemical heterogeneities detected today in the Earth's mantle could arise from ongoing partial melting in different mantle regions. A major open question, however, is the level of chemical stratification inherited from an early magma-ocean (MO) solidification. Here we show that the MO crystallized homogeneously in the deep mantle, but with chemical fractionation at depths around 1000 km and in the upper mantle. Our arguments are based on accurate measurements of the viscosity of melts with forsterite, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 68 publications
10
60
1
Order By: Relevance
“…The predicted values and anomalous decrease of the viscosity around 2,100-2,200 K are consistent with the results of experimental studies at pressures below ∼8 GPa (Cochain et al, 2017;Xie et al, 2020). However, three of the viscosity data reported by the experiments (Xie et al, 2020) (Karki & Stixrude, 2010). Our results can be represented by the modified VFT (Vogel-Fulcher-Tammann) equation (Harris et al, 2005) within two temperature ranges, η(P,T) = exp[−8.53 + 0.325 P − 0.0247 P 2 + (6851 − 651 P + 54.8 P 2 )/(T − 1000)] with 2200 ≤T ≤3000 K; and η(P,T) = exp[−8.00 + 0.00377 P − 0.000315 P 2 + (5470 + 123 P + 0.963 P 2 )/(T − 1000)], with 3500 ≤T ≤5000 K. The experimental data (Cochain et al, 2017;Xie et al, 2020) are compared with the predicted viscosity along 2,100 K using the VFT model.…”
Section: Viscosity Of Mgsio 3 Meltsupporting
confidence: 88%
“…The predicted values and anomalous decrease of the viscosity around 2,100-2,200 K are consistent with the results of experimental studies at pressures below ∼8 GPa (Cochain et al, 2017;Xie et al, 2020). However, three of the viscosity data reported by the experiments (Xie et al, 2020) (Karki & Stixrude, 2010). Our results can be represented by the modified VFT (Vogel-Fulcher-Tammann) equation (Harris et al, 2005) within two temperature ranges, η(P,T) = exp[−8.53 + 0.325 P − 0.0247 P 2 + (6851 − 651 P + 54.8 P 2 )/(T − 1000)] with 2200 ≤T ≤3000 K; and η(P,T) = exp[−8.00 + 0.00377 P − 0.000315 P 2 + (5470 + 123 P + 0.963 P 2 )/(T − 1000)], with 3500 ≤T ≤5000 K. The experimental data (Cochain et al, 2017;Xie et al, 2020) are compared with the predicted viscosity along 2,100 K using the VFT model.…”
Section: Viscosity Of Mgsio 3 Meltsupporting
confidence: 88%
“…Partial melting in the upper mantle creates heterogeneity between basaltic (magma) and harzburgitic (residue) end-members, forming a physically and chemically layered oceanic lithosphere. Subsequent injection into the mantle during subduction causes a non-equilibrated mantle that is a mechanical mixture of basalt and harzburgite (Allegre and Turcotte, 1986;Chris-tensen and Hofmann, 1994;Morgan and Morgan, 1999;Xu et al, 2008). Additional small-scale heterogeneity is introduced into the mantle by recycling of continental material through subduction and/or delamination.…”
Section: Introductionmentioning
confidence: 99%
“…Along with these developments, devising X-ray transparent cell in KMA is important as well in enhancing quality and capability of HPHT X-ray study. We demonstrated that BDD is an excellent heating material with high X-ray transparency 6,7 . However, transparent pressure medium, thermal insulator, and gasket are demanded as well to achieve high X-ray transparency in KMA experiment.…”
Section: Introductionmentioning
confidence: 87%